การออกแบบและพัฒนาเครื่องมือวิเคราะห์สมรรถนะระบบโทรศัพท์ไอพี - วุฒิพงศ์ กันแก้ว (จุฬาลงกรณ์มหาวิทยาลัย, 2003)
This research aims to develop a software that can analyze and report the performance of IP telephony this software provide a useful tools for network operators that need to management and fined tune the performance of IP telephony system. The tool collects and processes call detail record from IP voice gateways. The processed data is then stored in the tool database for analysis purpose. This tool can analyze answer seizure ratio, grade of service, call statistic, type of call problem, number of circuit in use, bandwidth usage. The analysis results can be display in graphic image, lined graph and table format. Users can obtain the analysis results either by selecting the up-to-date report or the traffic hiscory report or getting a warning window that is sorompted at a monitor every hour. The tool can be access via the internet using a standard web browser